2019
DOI: 10.26740/jggp.v17n2.p1-14
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Lokasi Exit Toll Jalan Tol Lingkar Luar Bogor Terhadap Perubahan Guna Lahan Di Sekitar Jalan Soleh Iskandar Kota Bogor

Abstract: Pembangunan infrastruktur jalan tol Lingkar Luar Bogor (BORR) merupakan bagian dari pengembangan kota Bogor dengan tujuan meningkatkan akses transportasi dari dan menuju Kota Bogor. Pengoperasian jalan tol ini sendiri berdampak pada perubahan penggunaan lahan di daerah yang dilintasi oleh jalan tol ini dan terutama pada daerah di sekitar lokasi Exit Toll. Penelitian ini bertujuan untuk mengukur besarnya area perubahan penggunaan lahan di area sekitar lokasi tol BORR. Penelitian ini menggunakan data penggunaan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Besides the linear sprawl type, one of the sprawl developments identified is the leapfrog sprawl development that has been converting some rice field areas into a settlement. Moreover, based on the literature review, the linear and leap sprawl patterns were also identified around the Bogor Outer Ring Road tolin precise, in the Kedung Halang (Susanto & Marsoyo, 2019). The existence of toll gates has caused land conversion in a radius of 0-1000 meters from the toll gates location, with the total area being more than 11,4 hectares.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the linear sprawl type, one of the sprawl developments identified is the leapfrog sprawl development that has been converting some rice field areas into a settlement. Moreover, based on the literature review, the linear and leap sprawl patterns were also identified around the Bogor Outer Ring Road tolin precise, in the Kedung Halang (Susanto & Marsoyo, 2019). The existence of toll gates has caused land conversion in a radius of 0-1000 meters from the toll gates location, with the total area being more than 11,4 hectares.…”
Section: Resultsmentioning
confidence: 99%
“…To add more discussion and observe the trends, the authors also did a literature review of some previous research related to the development caused by the existence of toll gates. The literature used include the literature review of Kedung Halang toll gate (Susanto & Marsoyo, 2019), Pejagan toll gate (Mukhlis & Soetomo, 2017) and Ungaran Timur toll gate (Aji et al, 2019;Nathania et al, 2017;Putro et al, 2019) The temporal scope of the literature review used in this research was quite varied, depending on the age of the toll gates. The area scope of the study used involved the toll roads situated on Jona island.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the study concentrated on the Jatiasih and Jatimekar Urban Villages, both located within a 1-kilometer radius of the Jatiasih toll gate (Figure 1). This 1 km radius was selected to evaluate the influence of the toll gate's operation on the surrounding land use related to economic activities, as supported by previous research [3,6,8].…”
Section: Research Areamentioning
confidence: 99%
“…The alteration in land use within urban areas have notable impact on human life, such as the enhancement of economic activities that result from toll road construction [4]. The expansion of transportation infrastructure is closely tied to the advancement of land use and economic activities [3,[5][6][7]. Toll road construction is expected to improve the welfare of the people, particularly those residing near the exit tolls [8].…”
Section: Introductionmentioning
confidence: 99%